Feasibility of transpedicular screw placement through the posterior arch of C1: A CT study in the Emirati population - Ivan James Prithishkumar; Dineshwary Suresh; Nerissa Naidoo; Rashid AlSharhan; Usama Al Bastaki; Jeyaseelan Lakshmanan; Baylis Vivek Joseph (Translational Research in Anatomy)
Background: Instrumentation of the lateral mass of first cervical vertebra (C1) is required in atlantoaxial instability. C1 bears a complicated relationship with adjacent neurovascular structures such as the vertebral artery and cervical spinal cord, which are at risk of injury in a misplaced screw. The objective of this study was to look at the feasibility of transpedicular screw placement into the C1 lateral mass with entry through the posterior arch. Methods: Computed tomography images of the cervical spine in 160 adults (>18 years) who are natives of the United Arab Emirates (UAE) (M = 80; F = 80) were reviewed. Morphometric parameters relevant to pedicle screw fixation via the posterior arch were studied. Results: Mean intraosseous distance from screw entry point in the posterior arch to the anterior cortex of lateral mass following a straight course without any inclination was 28.0 mm in males and 29.0 mm in females, allowing a safe distance of 3.2 mm from the foramen transversarium laterally and 9.0 mm from the vertebral canal medially. A medial inclination of 18° in males and 14° in females allows for increased bone purchase. Mean height of the pedicle at its junction with lateral mass was 5.6 mm in both sexes. However, the mean height of the posterior arch at the vertebral artery groove was 3.3 ± 0.4 mm in males and 3.1 ± 0.4 mm in females. Conclusion: We recommend placement of 3.5/4.0 mm screws using the notching technique, of length 28–30 mm with a slight medial angulation of 15° for increased bone purchase and greater stability of fixation.